Determinants of industrial output in Syria - Adel Mohsen; Soo Yean Chua; Normee Che Sab (Journal of Economic Structures, 2015)
This study attempts to investigate the determinants of industrial output in Syria over the period 1980 - 2010. The ADF unit root test, Johansen cointegration test, Granger causality test, impulse response functions, variance decomposition analysis, and stability tests are used in this study. The Johansen cointegration test indicates that industrial output is positively related to capital, manufactured exports, population and agricultural output, but negatively related to the oil price. Agricultural output has the biggest effect on industrial output. The Granger causality test indicates bidirectional causality between capital, oil price, manufacturing exports, population, agricultural output, and industrial output in the short and long run.
Keywords: O11; E20; 330; Oil-dependent economy; Industrial output; Capital; Manufactured exports; Oil price; VAR